2020
DOI: 10.1038/s41598-020-77013-1
|View full text |Cite|
|
Sign up to set email alerts
|

Association of hyperuricemia and gamma glutamyl transferase as a marker of metabolic risk in alcohol use disorder

Abstract: Excessive alcohol consumption leads to overproduction of urates and renal function plays a critical role in serum uric acid levels. We aimed to assess associations of hyperuricemia in patients with alcohol use disorder (AUD) and comparable Glomerular Filtration Rate (GFR). A total of 686 patients undergoing treatment for AUD between 2013 and 2017 were eligible (77% men); age at admission was 47 years [interquartile range (IQR), 40–53 years], age of onset of alcohol consumption was 16 years [IQR, 16–18 years] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Therefore, secondary hyperuricemia can be induced by an excessive intake of purine-rich food (e.g., red meat, offal, seafood) [21], cellular degradation processes, and high cell turnover in the context of leukemia/lymphoma [22] or anticancer treatment with chemo-or radiation therapy [23], which all increase the availability of free purines. In addition to a diet high in purines, other lifestyle-related behaviors such as excessive intake of fructose [24,25] and alcohol abuse [26,27] can also trigger hyperuricemia, which explains the high prevalence in industrialized countries and the increasing prevalence in developing countries [28]. Aside from the aforementioned environmental factors, also genetic defects in enzymes responsible for the biotransformation of purine bases can favor primary hyperuricemia, as is the case in Lesch-Nyhan or Kelley-Seegmiller syndromes [29].…”
Section: Gout and Hyperuricemiamentioning
confidence: 99%
“…Therefore, secondary hyperuricemia can be induced by an excessive intake of purine-rich food (e.g., red meat, offal, seafood) [21], cellular degradation processes, and high cell turnover in the context of leukemia/lymphoma [22] or anticancer treatment with chemo-or radiation therapy [23], which all increase the availability of free purines. In addition to a diet high in purines, other lifestyle-related behaviors such as excessive intake of fructose [24,25] and alcohol abuse [26,27] can also trigger hyperuricemia, which explains the high prevalence in industrialized countries and the increasing prevalence in developing countries [28]. Aside from the aforementioned environmental factors, also genetic defects in enzymes responsible for the biotransformation of purine bases can favor primary hyperuricemia, as is the case in Lesch-Nyhan or Kelley-Seegmiller syndromes [29].…”
Section: Gout and Hyperuricemiamentioning
confidence: 99%
“…Hyperuricemia has been associated with MetS and coronary artery disease regardless of alcohol consumption 37 , 38 . As for the association between SUA and MetS, a recent study by our group described a close relationship between hyperuricemia and serum GGT in AUD patients 15 . Furthermore, individuals with elevated SUA levels are at risk of developing chronic renal dysfunction according to a systematic review including 13 studies and 190.000 participants 39 .…”
Section: Discussionmentioning
confidence: 97%
“…Five percent of the population aged 15 to 64 years presented a pattern of at-risk alcohol consumption in Spain and alcohol was responsible for 35% of treatment admissions in addiction units 12 . Furthermore, one in five people with alcohol use disorder (AUD) have MetS and studies have identified geographic differences in relation with life styles and environmental factors 13 due to arterial hypertension and dyslipidemia, among other mechanisms 14 , 15 . Moreover, unhealthy lifestyles (i.e., sedentarism, tobacco smoking) may be relatively frequent in individuals with alcohol misuse.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia has been associated with MetS and coronary artery disease regardless of alcohol consumption (34,35). As for the association between SUA and MetS, a recent study by our group described a close relationship between hyperuricemia and serum GGT in AUD patients (14). Furthermore, individuals with elevated SUA levels are at risk of developing chronic renal dysfunction according to a systematic review including 13 studies and 190.000 participants (36).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive alcohol consumption has been associated with each of the components of MetS; speci cally, alcohol abuse is associated with a higher risk of CVD due to arterial hypertension and dyslipidemia, among other mechanisms (13,14). Moreover, unhealthy lifestyles (i.e., sedentarism, tobacco smoking) may be relatively frequent in individuals with alcohol misuse.…”
Section: Introductionmentioning
confidence: 99%